Chaotic Behaviours in Dynamical Systems with Application to Secure Communication (2012)
Attention has recently been focused on irregular aspects of the behaviour of dynamical systems. One of such behavioural modes is chaos which has been widely reported as having a great potential in communications. This study aimed at demonstrating the major concepts in non-linear dynamics and chaos and the application of these properties in communication. The behavioural modes of logistic map which is a simple dynamical system were investigated with different values of system parameters and initial conditions by computer simulation using Microsoft Excel. The simulation results indicated the sensitivities of the logistic map to parameter changes as well as variations in the initial conditions. The noise-like chaotic trajectory obtained for certain parameter value was employed in masking a message signal. The resulting signal confirmed the potential application of chaos in secure communication.